2018
DOI: 10.1386/jmte.11.1.5_1
|View full text |Cite
|
Sign up to set email alerts
|

Technology’s role for achieving creativity, diversity and integration in the American undergraduate music curriculum: Some theoretical, historical and practical perspectives

Abstract: This article provides an overview of six years of research with the goal of identifying key music technology competencies seen as essential for the undergraduate music major by tertiary music professors largely in North America. The results of the research are viewed from multiple dimensions: ‘pillars’ of curriculum as defined by a recent College Music Society (CMS) (United States) task force report, the diffusion of innovative technology historically within music instruction and general categories of music st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Curriculum design emphasized a trend for creative technical learning within the discipline of music technology, focused primarily on music production skills. This emphasis aligns with core music technology competencies identified by Webster and Williams (2018, p. 25) in the North American context. When mapped against an employability attributes framework, courses from sample institutions all demonstrated Novel and Adaptive Thinking, Computational Thinking, New Media Literacy, and Design Mindset in course LOs.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Curriculum design emphasized a trend for creative technical learning within the discipline of music technology, focused primarily on music production skills. This emphasis aligns with core music technology competencies identified by Webster and Williams (2018, p. 25) in the North American context. When mapped against an employability attributes framework, courses from sample institutions all demonstrated Novel and Adaptive Thinking, Computational Thinking, New Media Literacy, and Design Mindset in course LOs.…”
Section: Resultssupporting
confidence: 62%
“…In relation to music, and music technology, McKoy (2009) has suggested that music can be a source of cultural identity for many groups and communities and is one of several expressive forms through which cultures of the world, and microcultures within specific locations, may be known and understood. Similarly, the College Music Society Task Force Report asserts “that multiple dimensions of diversity must be embedded into the content and process of undergraduate education” which encompasses “an expanding, interconnected global society with cross-cultural influences and cross-over stylistic expressions” (Sarath, Myers, & Campbell, cited in Webster & Williams, 2018, pp. 7–8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works were devoted to various aspects of pedagogical innovations in the field of art education, new forms and technologies of art pedagogy: various aspects of creative interaction between a teacher and children (Kim, Morton, & Gregorio, 2019); questions of the effectiveness of digital technologies in education (Forsler, 2018;Duisenbayev, Daumov, & Kuzdybayeva, 2018), as well as the inclusive art education of bedridden children (Koptseva, 2018); innovative technologies in the American undergraduate music program (Webster & Williams, 2018); the importance of improvisation and composition in the musical development of schoolchildren as a leading component in the new educational technology in music lessons (Alekseeva & Usacheva, 2018); the integration of arts and science, technology, technology and mathematics (STEM) (Kinsella, 2018); solving the problem of leisure culture -the perception of the environment as a place for learning and enjoying (Veledo, Belen, Manrique Lopez, & Fombella Coto, 2018); improving the vocal skills of future teachers (Jia, 2016), the development of giftedness (Nogaj & Bogunovic, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…We review three examples of these studies, relating to the perceived technological requirements of undergraduate musicians, students of music education and intending audio engineers respectively. Webster and WIlliams (2018) conducted a six-year study intended to identify core technology competencies for undergraduate music students. The authors use 'competence' to describe the "critical understandings that underpin the application of the music technology skills" (2018, p. 22).…”
Section: Introductionmentioning
confidence: 99%